Karakteristik Keluarga, Ketahanan Pangan, Pengeluaran Pangan, dan Keanekaragaman Pangan Keluarga dengan dan tanpa WaSt (Wasting-Stunting) pada Anak di Kota Semarang: Family Characteristics, Food Security, Expenditure, and Dietary Diversity among Families with and without Concurrently Wasted and Stunted Children in Semarang - Purwanti, Rachma; Ginting, Ignasia Agatha Br; Aulia, Nurhanna Putri; Nuryanto, Nuryanto; Dieny, Fillah Fithra (Amerta Nutrition, 2024)
Background: Family characteristics, food security, expenditure, and diversity are indirectly associated with children's nutritional status. Objectives: This study aimed to examine the differences between food security, expenditure, and diversity among children under five with and without concurrent wasting and stunting (WaSt) in Semarang City. Methods: This study utilized an observational analytic approach with cross-sectional design. Subject selection using a consecutive sampling method obtained 72 subjects consisting of 18 subjects in each group of normal, stunted, wasted, and concurrently wasted and stunted (WaSt). Structured questionnaires collected data on the characteristics of fathers, mothers, and families. Interviews were conducted using the Household Food Insecurity Access Scale (HFIAS), which was obtained to measure food security among families. In contrast, the Individual Dietary Diversity Score (IDDS) was used to obtain food diversity. Differences were analyzed using one-way ANOVA and the Kruskal-Wallis test. A confidence level of 95% was utilized, and the results were significant, with a p-value<0.05 Results: There were significant differences in age, maternal nutrition knowledge, family income, food security, food expenditure, and food diversity between children under five with and without WaSt (p-value=0.010; 0.002; 0.026; 0.001; <0.001; 0.021). Conclusion: The WaSt group has a different age composition, maternal nutritional knowledge, family income, food security, food expenditure, and food diversity from other groups.